Local Ionic Displacements and Polarization at the Paraelectric‐Ferroelectric Heterointerface: Effect of Octahedral Distortion. Issue 25 (10th August 2022) - Luo, Jin; Qian, Hao; Zheng, Tianyang; Li, Jing‐Feng; Liu, Yunfei; Lyu, Yinong
Abstract: At the ferroelectric ABO3 perovskite heterointerface, the broken translational symmetry significantly alters the octahedral network and cation sublattices. Experimentally revealing the interaction between the polarization and atomic structure parameters is beneficial not only for understanding the novel physical phenomena but also for realizing exotic physical functionalities at the materials surface science. Here, it is demonstrated that the induced polarization can be realized by the cooperative interaction between the octahedral distortion and the cation sublattices at the paraelectric‐ferroelectric heterointerface in the (K, Na)NbO3 epitaxial thin film. It is found that the cation–cation displacement scales with the tetragonality of the perovskite unit cell but not with the polarization, which is minimal in the substrate but increases substantially in the thin film. Nevertheless, the oxygen octahedral distortion in the substrate, accompanied by octahedral rotation, is stronger than that in the film, resulting in a translated and stable polarization across the interface. These results demonstrate the octahedral network plays a significant role in the ferroelectric polarization and can also greatly advance the understanding of the heterointerface science for ferroelectrics. Abstract : The cation–cation displacement gradually increases across the paraelectric‐ferroelectric heterointerface and scales with the tetragonality of the perovskite unit cell but not with the polarization. However, the oxygen octahedral distortion, accompanied by octahedral rotation, leads to the comparable cation–oxygen displacement in the substrate with that in the film, resulting in a translated and stable polarization across the interface.